2013
DOI: 10.1126/science.1239745
|View full text |Cite
|
Sign up to set email alerts
|

Shape Memory and Superelastic Ceramics at Small Scales

Abstract: Shape memory materials are a class of smart materials able to convert heat into mechanical strain (or strain into heat), by virtue of a martensitic phase transformation. Some brittle materials such as intermetallics and ceramics exhibit a martensitic transformation, but fail by cracking at low strains and after only several applied strain cycles. Here we show that such failure can be suppressed in normally brittle martensitic ceramics by providing a fine-scale structure with few crystal grains. Such oligocryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
204
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 267 publications
(215 citation statements)
references
References 30 publications
9
204
0
2
Order By: Relevance
“…3b). The large linear elastic strain rivals the maximum strain (8%) of shape-memory materials such as NiTi alloys and zirconia ceramics 26,27 . Furthermore, although the material is elastically 'soft' (highly compressible), it has an ultrahigh strength over 1 GPa because of the remarkably wide elastic regime.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3b). The large linear elastic strain rivals the maximum strain (8%) of shape-memory materials such as NiTi alloys and zirconia ceramics 26,27 . Furthermore, although the material is elastically 'soft' (highly compressible), it has an ultrahigh strength over 1 GPa because of the remarkably wide elastic regime.…”
Section: Resultsmentioning
confidence: 99%
“…Under triaxial deformation, type-II GC exhibits both ultrahigh compressive strength (above 1 GPa) and superelasticity (recoverable linear strain up to 6%, comparable to, or even beyond, common shape-memory alloys and ceramics 26,27 ). To understand the remarkably high compressibility and superelastic behaviour of type-II GC, we need to examine the interaction of the structural components in GC.…”
Section: Discussionmentioning
confidence: 99%
“…13 Since small grains tend to F o r P e e r R e v i e w 3 suppress the martensitic transformation, when such polycrystals are subjected to applied stress, cracks are generally initiated before achieving observable shape deformation via the transformation. On the other hand, in our recent work 14 , we showed that for small-volume samples with a length scale reduced to a few micrometers, zirconia ceramics will have an oligocrystalline structure and can exhibit significantly enhanced shape memory properties without cracking. In that work, we used Ce-containing zirconia with a grain size of about 2 µm.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to experience significant shape deformation and recovery has made shape memory materials highly attractive for military, medical, aerospace and robotics applications [6e8]. Recently we reported a new class of shape memory ceramics: micron-sized single-crystal zirconia [9]. These ceramics exhibit strains comparable to metals but have higher strength and potentially higher operating temperatures than metals [10,11] for applications like solid state actuators [12].…”
Section: Introductionmentioning
confidence: 99%